Brain Microvascular Endothelial Cell-Derived HMGB1 Facilitates Monocyte Adhesion and Transmigration to Promote JEV Neuroinvasion - Zou, Song-Song; Zou, Qing-Cui; Xiong, Wen-Jing; Cui, Ning-Yi; Wang, Ke; Liu, Hao-Xuan; Lou, Wen-Juan; Higazy, Doaa; Zhang, Ya-Ge; Cui, Min (Frontiers in Cellular and Infection Microbiology, 2021)
Infection with the Japanese encephalitis virus (JEV) induced high morbidity and mortality, even caused permanent neurological sequelae. However, the mechanisms of virus invasion, from the bloodstream to the brain through a mature endothelium, remains elusive. Here, we showed that extracellular HMGB1 facilitates immune cells transendothelial migration. Furthermore, it is observed that the migration of immune cells into the CNS dramatically increased during JEV infection which may benefit viral clearance, but paradoxically accompanied by the expedite onset of Japanese encephalitis (JE) in advance. Brain microvascular endothelial cells were utilized for the detection of HMGB1 release in vitro, and the measurement of endothelial cell activation and cell adhesion, the integrity of the BBB. A genetically modified JEV expressing EGFP (EGFP-JEV) and the BBB model were used to trace the JEV-infected immune cells transmigration to mimic the process of virus neuroinfection. We find that JEV causing HMGB1 released from BMEC and increasing adhesion molecules. Recombinant HMGB1 enhances leukocyte-endothelium adhesion, facilitating JEV-infected monocytes transmigrate across endothelia. Thus, JEV successfully utilized the monocyte to spread the virus to the brain, expanding the brain infection, leading to the acceleration of JE onset, which was facilitated by HMGB1. HMGB1-promoted monocyte transmigration may represent the mechanism of JEV neuroinvasion, which could be targets for therapy.